Entire Encapsulation of Thymopentin by Extended Biphen[3]arene Carboxylate for Improving Plasma Stability - Keming Ren; Junyi Chen; Chunju Li (Molecules)
Peptide-based therapy is appealing in modern medicine owing to its high activity and excellent biocompatibility. Poor stability, leading to unacceptable bioavailability, severely constrains its clinical application. Here, we proposed a general supramolecular approach for improving the plasma resistance of a commercially available peptide agent, thymopentin. The 1H NMR results indicated that the large-sized extended biphen[3]arene carboxylate (ExBP3C) can entirely encapsulate this peptide at its main chain with a binding stoichiometry of 1:1 and Ka value of (1.87 ± 0.15) × 105 M−1, which varied radically from recognizing specific amino acid residues by carboxylatopillar[5]arene (CP5A). Notably, host–guest complexation by ExBP3C could maintain 24.85% of the original thymopentin amount for 60 min in the presence of rat plasma, whereas free thymopentin, or co-dosed with CP5A and cucurbit[7]uril, underwent rapid degradation and became undetectable within just 30 min. In addition, cytotoxicity and hemolysis assays preliminary demonstrated that the employment of ExBP3C as a supplementary material was relatively nontoxic at a cellular level.